2020
DOI: 10.1002/jbt.22671
|View full text |Cite
|
Sign up to set email alerts
|

Surface modifications affect iron oxide nanoparticles' biodistribution after multiple‐dose administration in rats

Abstract: Iron oxide nanoparticles (IONPs) possess many utilizable physical and chemical properties and have an acceptable level of biocompatibility. Therefore, they are extensively used in different medical applications. Hence, the challenge is to modify the surfaces of prepared iron oxide nanoformulations with a biocompatible coat to enhance their biosafety. In this study, different formulations of IONPs with different capping agents (citrate [Cit‐IONPs], curcumin [Cur‐IONPs], and chitosan [CS‐IONPs]) were prepared an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In addition, aspects related to the biodistribution of iron oxide nanoparticles coated with different materials have been studied recently [ 34 , 35 , 36 , 37 , 38 , 39 ]. In their study regarding the “Genotoxicity and biocompatibility of superparamagnetic iron oxide nanoparticles: influence of surface modification on biodistribution, retention, DNA damage and oxidative stress”, Gosh et al [ 34 ] reported the use of poly (lactic-co-glycolic acid) together with either didodeclydimethyl-ammonium-bromide or α-tocopheryl-polyethleneglycol-succinate in order to reduce the cytogenotoxicity and the generation of reactive oxygen species of iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aspects related to the biodistribution of iron oxide nanoparticles coated with different materials have been studied recently [ 34 , 35 , 36 , 37 , 38 , 39 ]. In their study regarding the “Genotoxicity and biocompatibility of superparamagnetic iron oxide nanoparticles: influence of surface modification on biodistribution, retention, DNA damage and oxidative stress”, Gosh et al [ 34 ] reported the use of poly (lactic-co-glycolic acid) together with either didodeclydimethyl-ammonium-bromide or α-tocopheryl-polyethleneglycol-succinate in order to reduce the cytogenotoxicity and the generation of reactive oxygen species of iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the clinical translation of these drug delivery systems is also not clear because most of the related research has been conducted on the level of cell culture, with limited preclinical studies that actually determine the fate of the particles. The fate of magneto‐responsive nanoparticles, after the degradation of the lipid matrix and the subsequent clearance of the iron oxide nanoparticles from the body is another concern (Fahmy et al, 2021; A. Zhang et al, 2020). Studies have reported that IONPs are likely to be biocompatible however it strongly relies on their physicochemical properties including the particle size and surface modification (Feng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[135] IONP Surface modifications affect iron oxide NP biodistribution in rats. [136] AgNP Single silver nanoparticle instillation induced early and persisting moderate cortical damage in rat kidneys. [134] AgNP AgNPs could interact with the anatomical structures of the kidney to induce injury.…”
Section: Agnpmentioning
confidence: 97%
“…The ferrous sulfate (FeSO4)-treated group showed the highest kidney iron accumulation as compared with the other groups. The histopathological examination revealed that signs of toxicity were predominant for groups treated with Cit-IONPs or commercial FeSO 4 [ 136 ].…”
Section: Nanotoxicologymentioning
confidence: 99%